Annotated record of the detailed examination of Mn deposits from DSDP Leg 85 (Holes 572D, 573D, 574D ) - L Mayer; Fritz Theyer (PANGAEA, 1985)
SDP Leg 85 was designed to take advantage of a new hydraulic piston corer (HPC) enabling to recover fairly undisturbed samples from the upper 100 to 300 m and thus to carry out high resolution stratigraphic studies. The JOIDES Ocean Paleoenvironment Panel selected five drill sites, two sites (571 and 572) are in the eastern Pacific, and the three others (573, 574, and 575) form a north-south line that lies at approximately 133°W across the equatorial high productivity zone.